ONLINE LEAKAGE CURRENT MONITORING SYSTEM USING TIMEFREQUENCY DISTRIBUTION ON HIGH VOLTAGE INSULATOR - Zainal Abidin, Nur Qamarina; Abdullah, Abdul Rahim; NORDDIN, NURBAHIRAH; Aman , Aminudin (2012)
Leakage current frequency components are frequently used as a tool for surface condition monitoring on polymeric insulation material and their pollution severity. Fast Fourier Transform (FFT) is one of the methods that are applied for the analysis, but it has some limitation in non-stationary signal. This paper presents the analysis of leakage current via online monitoring system for high voltage application. Tracking and erosion test complying with BS EN 60587-2007 is conducted on polymeric insulation to monitor the set of different leakage current patterns from capacitive, resistive and non-linear activities. The information obtained from this online monitoring allows the user to identify leakage current performance in real time. The user can monitor the performances at certain distances safely which it is the main purpose for online monitoring besides the accuracy of the measurement system, time and cost saving.